Stylisation in rethinking history through chronotope and polyphony in selected postmodern Indian thriller novels in english - Pathinathan, Santini (2021)
Fiction writers have always been fascinated with history, especially historical fiction writers or writers who are inspired by history. It is, however, quite rare to have a novel that merges imagination and history to make it seem real. The selected novels are able to do just that. They have merged ancient history and imagination to re-present history. This research studies Ashwin Sanghi’s novels Chanakya’s Chant (2010) and The Krishna Key (2012) and Christopher Doyle’s The Mahabharata Secret (2013) and The Mahabharata Quest: The Alexander Secret (2014). These novels have been chosen because there is a surge in the thriller genre known as Bharathi Fantasy in India today. However, there has been a lack of research on the thriller genre, especially in terms of writing style, and as such, the current study hopes to explore the area of stylisation in rethinking history through thrillers that concurrently portray the glorious past and the current situation in the country in the form of novels. This study aims to explore the portrayal of chronotopes in the selected novels and investigate the multiple voices within the novels to show how history is rethought using the concepts of the chronotope and polyphony to develop the plots. This has ultimately led the researcher to finally show how the writers use Bakhtin’s five features of stylisation to stimulate the rethinking of history. This study employs Bakhtin’s chronotope and polyphony concepts to analyse plot development and to investigate the stylisation in the authors’ writing to show how history is rethought. The findings show that the chronotope of crisis/threshold is the most prevalent in moving the plots in these thriller novels besides the chronotope of castle, which emphasises historical elements. Next, this study also shows that each character moves the plot from his or her perspective. Besides that, polyphony can also be used to show how history is rethought because throughout the novels, the findings show history being discussed by different characters and also by the authors themselves. Though the authors’ voices maybe indirect, their intentions seem very clear through their writing styles, which conform to all five features of Bakhtin’s stylisation. Through the five features of stylisation, we can read the writers’ voices as they narrate events. Besides that, the second feature shows the voices of the characters. The third feature involves the various forms of semi-literary (written) everyday narration that is used in the selected novels, and the fourth feature relates to the extra-artistic authorial speech which the selected novels include as philosophical records, archaeologic records and so on. And finally, the fifth feature shows the characters’ thoughts. All these features bring the characters to life and make the plots vivid, thus stimulating the reader to rethink history.